Exploring the interplay of management, quality and ethics in addressing gender and school-based disparities in students’ research self-efficacy and anxiety - Maame Afua Nkrumah; Ronald Osei Mensah; Alwyna Sackey Addaquay (Discover Education)
Abstract The study sought to examine the gender, faculty and school-based disparity that exists in students’ research self-efficacy, perception of ethics in research and the level of stress they face in conducting research. A sample of 385 undergraduate students from the faculty of business and hospitality were selected from three public universities in Ghana, namely the University of Education, Winneba, Takoradi Technical University and Kumasi Technical University (UEW, TTU and KsTU). The Logit regression model, Mann-Whitney U test and Chi-square of association were employed for the analysis. The findings indicate that 68.4% of female students reported higher research self-efficacy compared to 57.2% of males, showing a significant gender disparity (p < 0.05). Regarding research ethics, 75.6% of students relied on past research works, with notable differences across faculties (p = 0.03). Perceptions of plagiarism detection software availability revealed that 62.8% of KsTU students believed the software was accessible compared to 48.2% and 50.6% for UEW and TTU, respectively (p < 0.01). Additionally, 58.3% of students cited limited access to supervisors as a major challenge, with hospitality students experiencing higher stress levels (72.1%) compared to business students (54.5%) (p < 0.001). However, all students experienced stress in undertaking research. The findings further indicated that there was a gender-based disparity in all of the assessment factors.